2018
DOI: 10.3892/mco.2018.1632
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of extended liver resections for colorectal liver metastasis compared with standard liver resections

Abstract: Abstract. Colorectal liver metastatic lesions sometimes invade adjacent organs. A hepatectomy is often extended to include the involved adjacent organ to achieve negative surgical margins. The purpose of the present retrospective study was to evaluate the surgical outcomes of extended liver resections and patients' prognoses. The medical records of 178 patients with colorectal liver metastasis who underwent liver resections in the Department of Gastroenterological Surgery at Osaka University Hospital (Suita, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
1
16
0
5
Order By: Relevance
“…Comparative studies assessing outcomes of MLRs are scarce, 7,27 and the available data regarding perioperative morbidity and In our series, overall morbidity was 41.5% in MLR group, not significantly different from isolated hepatectomy group (31.1%). This finding was reported by some authors, 7,9 but others found higher morbidity in combined resections. 10,27 Despite no difference in overall morbidity, our results confirm that MLRs are major procedures associated with longer operative time, higher blood loss, and longer hospital stay when compared with well-matched controls submitted to similar liver resections, which is in accordance to previously published data.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Comparative studies assessing outcomes of MLRs are scarce, 7,27 and the available data regarding perioperative morbidity and In our series, overall morbidity was 41.5% in MLR group, not significantly different from isolated hepatectomy group (31.1%). This finding was reported by some authors, 7,9 but others found higher morbidity in combined resections. 10,27 Despite no difference in overall morbidity, our results confirm that MLRs are major procedures associated with longer operative time, higher blood loss, and longer hospital stay when compared with well-matched controls submitted to similar liver resections, which is in accordance to previously published data.…”
Section: Discussionsupporting
confidence: 84%
“…[16][17][18][19] In a recent study, Dias et al 20 MLRs are rare procedures even in high-volume centers, with frequencies varying from 1% to 11.2%. 7,9,12,24 Hand et al 7 are used in the literature: "multivisceral," "multiorgan," or "extended resection." 5,9 Keeping in mind the limitations and impropriety of the term, as not only "visceras" (eg, VCI and diaphragm) were included in MLR group, we choose de term "multivisceral" since it is the most commonly employed in the literature.…”
Section: Subgroup Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the rates of laparoscopic and robotic major liver resections have increased, and controlling blood loss during these minimally invasive surgeries is difficult; to address this, several studies have recently been published to introduce different methods of the PM in laparoscopic or robotic surgeries [16][17][18] . In addition, the risk of intraoperative bleeding, perioperative blood infusion, postoperative complications, and mortality after EH are still considerable 5,24,25 .…”
Section: Discussionmentioning
confidence: 99%